Expression of novel extracellular sulfatases Sulf-1 and Sulf-2 in normal and osteoarthritic articular cartilage - Otsuki, Shuhei (BioMed Central, 2008)
INTRODUCTION: Changes in sulfation of cartilage glycosaminoglycans as mediated by sulfatases can regulate growth factor signaling. The aim of this study was to analyze expression patterns of recently identified extracellular sulfatases Sulf-1 and Sulf-2 in articular cartilage and chondrocytes. METHODS: Sulf-1 and Sulf-2 expressions in human articular cartilage from normal donors and patients with osteoarthritis (OA) and in normal and aged mouse joints were analyzed by real-time polymerase chain reaction, immunohistochemistry, and Western blotting. RESULTS: In normal articular cartilage, Sulf-1 and Sulf-2 mRNAs and proteins were expressed predominantly in the superficial zone. OA cartilage showed significantly higher Sulf-1 and Sulf-2 mRNA expression as compared with normal human articular cartilage. Sulf protein expression in OA cartilage was prominent in the cell clusters. Western blotting revealed a profound increase in Sulf protein levels in human OA cartilage. In normal mouse joints, Sulf expression was similar to human cartilage, and with increasing age, there was a marked upregulation of Sulf. CONCLUSION: The results show low levels of Sulf expression, restricted to the superficial zone in normal articular cartilage. Sulf mRNA and protein levels are increased in aging and OA cartilage. This increased Sulf expression may change the sulfation patterns of heparan sulfate proteoglycans and growth factor activities and thus contribute to abnormal chondrocyte activation and cartilage degradation in OA.